Mesocrystalline coordination polymer as a promising cathode for sodium-ion batteries. Issue 9 (21st December 2015) - Meng, Qi; Zhang, Wei; Hu, Ming; Jiang, Ji-Sen
Abstract : Prussian blue (PB) mesocrystals with Na as the alkaline metal were synthesized and used for as cathodes in Na-ion batteries. The mesocrystalline structure endowed PB with very different phase change behavior and electrochemical performance in contrast to PB single-crystals in cyclic voltammograms and galvanostatic discharge/charge voltage profiles of PB/Na half-cells. Abstract : Prussian blue (PB) mesocrystals with Na as the alkaline metal were synthesized and used as cathode materials in Na-ion batteries. The mesocrystalline structure endowed PB with very different phase change behavior and electrochemical performance in contrast to PB single-crystals in cyclic voltammograms and galvanostatic discharge/charge voltage profiles of PB/Na half-cells.